Lamination Theory and Application - Osheku, Charles A. (IntechOpen, 2018)
The field of lamination has developed significantly over the past 5000 years. Nowadays, we have a humongous array of structures and technological systems where composite laminates are applied. From the viewpoint of structural mechanics, an interface slip motion between two laminated structures, such as beam plate and plate in the presence of dry friction, can be utilized for slip damping systems. By scientific definition, slip damping is a mechanism exploited for dissipating noise and vibration energy in machine structures and systems. Researchers have developed several mathematical models for noise dissipation, minimization and complete vibration isolation laminated mechanisms. The purpose of this book is to describe new concepts of producing laminated structures and possible modern engineering applications.